Seed Quality as Influenced by Seed Treatment, Packing Material and Storage Condition of China aster (Callistephus chinensis) - SHANTAPPA TIRAKANNANAVAR; RC JAGADEESHA; PM MUNIKRISHNAPPA; ASHOK (Seed Research, 2026)
An investigation was carried out with to study the influence of seed treatment with Captan and Bavistin, packed in polythene bag and paper bag and stored under cold storage and ambient condition, on storability of china aster seeds. Seeds treated with bavistin (T₂) recorded significantly higher germination percentage (65.50%), shoot length (2.48cm), root length (4.56cm), seedling length (7.03 cm), seedling dry weight (16.05 mg) and seedling vigour index (465) at the end of nine months of storage. With respect to packing materials, the seeds packed in polythene bag (700 gauge) recorded higher germination percentage, shoot length, root length, seedling length, seedling dry weight, seedling vigour index and lower moisture content of seed at the end of nine months of storage (71.78%, 2.34cm,4.52cm, 6.80 cm, 15.86 mg, 495 and 6.18%, respectively). Similarly the seeds stored in refrigerated condition (S₂) recorded significantly higher germination percentage (69.78%), shoot length (2.36cm), root length (4.56cm), seedling length (6.92 cm) and seedling vigour index (486) at the end of ninth months of storage. Seedling dry weight had no significant effect on storage condition at the end of ninth months of storage. The treatment combinations T x P, T XS, P x S and T x P x S showed significant effect only for seedling vigour index